#TITLE_ALTERNATIVE# - MIRZA AQUARIO (NIM 12203026), MUHAMAD
The development of IPR equation usually using cylindrical reservoir model, homogeneous, isotropic, horizontal layer and only has one well in the middle that cut all the productive layer. But there is no research done about the development of IPR curves for two phase tilted reservoir that has been predicted to have own characterization because the process of freed segregation gas. The objective of this final project is to develop IPR curve based on well test data and improve the equation for future IPR curve prediction at two phase tilted reservoir, where the driving force is solution gas. When the reservoir is tilt, the gas segregation will occurred at production time and separate from the oil and move to the top of the tilted reservoir. This gas segregation will change the characteristic of reservoir and change the model that determine the dimensionless IPR curve to the well in tilted reservoir. The development of dimensionless IPR curve for tilted reservoir is with single well model system in tilted reservoir using CMG simulator. The research is using data as used at Vogel's and produce the dimensionless IPR curve equation and than developed to future IPR curve equation prediction. With that model simulate the development of IPR curve and get the correlation of IPR curve equation when do the well test and prediction of future IPR curve,that made both of them simple equation. The suggest equation compared with Vogel's equation and equation of future IPR curve prediction.